A20-binding inhibitor of NF-κB (ABIN1) controls Toll-like receptor-mediated CCAAT/enhancer-binding protein β activation and protects from inflammatory disease - Zhou, Jingran (National Academy of Sciences, 2011)
Toll-like receptors (TLRs) are expressed on innate immune cells and trigger inflammation upon detection of pathogens and host tissue injury. TLR-mediated proinflammatory-signaling pathways are counteracted by partially characterized anti-inflammatory mechanisms that prevent exaggerated inflammation and host tissue damage as manifested in inflammatory diseases. We biochemically identified a component of TLR-signaling pathways, A20-binding inhibitor of NF-κB (ABIN1), which recently has been linked by genome-wide association studies to the inflammatory diseases systemic lupus erythematosus and psoriasis. We generated ABIN1-deficient mice to study the function of ABIN1 in vivo and during TLR activation. Here we show that ABIN1-deficient mice develop a progressive, lupus-like inflammatory disease characterized by expansion of myeloid cells, leukocyte infiltrations in different parenchymatous organs, activated T and B lymphocytes, elevated serum Ig levels, and the appearance of autoreactive antibodies. Kidneys develop glomerulonephritis and proteinuria, reflecting tissue injury. Surprisingly, ABIN1-deficient macrophages exhibit normal regulation of major proinflammatory signaling pathways and mediators but show selective deregulation of the transcription factor CCAAT/enhancer binding protein β (C/EBPβ) and its target genes, such as colony-stimulating factor 3 (Csf3), nitric oxide synthase, inducible (Nos2), and S100 calcium-binding protein A8 (S100a8). Their gene products, which are intimately linked to innate immune cell expansion (granulocyte colony-stimulating factor), cytotoxicity (inducible nitric oxide synthase), and host factor-derived inflammation (S100A8), may explain, at least in part, the inflammatory phenotype observed. Together, our data reveal ABIN1 as an essential anti-inflammatory component of TLR-signaling pathways that controls C/EBPβ activity.